2018
DOI: 10.1097/wnr.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Association between glutamate/glutamine and blood oxygen level dependent signal in the left dorsolateral prefrontal region during verbal working memory

Abstract: Functional MRI (fMRI) has provided much insight into the changes in the neuronal activity on the basis of blood oxygen level dependent (BOLD) phenomenon. The dynamic changes in the metabolites can be detected using functional proton magnetic resonance spectroscopy (H-fMRS). The strategy of combining fMRI and H-fMRS would facilitate the understanding of the neurochemical interpretation of the BOLD signal. The dorsolateral prefrontal region is critically involved in the processing of working memory (WM), as demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several other studies have reported positive associations, BOLD responses and glutamatergic metabolite concentrations [ 83 , 84 ]; however, a recent systematic review reports no coherent relationship between glutamate and BOLD activation [ 83 ]. One possible reason for this could be that the majority of studies did not separate Glu and Gln due to methodological difficulties, but rather report the two compounds together as Glx.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported positive associations, BOLD responses and glutamatergic metabolite concentrations [ 83 , 84 ]; however, a recent systematic review reports no coherent relationship between glutamate and BOLD activation [ 83 ]. One possible reason for this could be that the majority of studies did not separate Glu and Gln due to methodological difficulties, but rather report the two compounds together as Glx.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate reuptake in glia accounts for ~50% of energy expenditure in the brain [ 17 ], so that changes in glutamate/glutamine cycling and energy expenditure are highly correlated [ 18 21 ]. The increased energy expenditure, in turn, leads to an increase in local cerebral blood flow that can be detected using BOLD imaging [ 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glu plays a major role during activity-dependent energy demands as the most abundant aminoacid and the main excitatory neurotransmitter in the brain (Ligneul et al, 2021). Increasing evidence demonstrates the close regulation between glucose consumption and glutamateglutamine cycling (Sibson et al, 1998;Rothman et al, 2003), which was theorised to lead to increasing Glu levels during the BOLD-activation period (Betina Ip et al, 2017;Vijayakumari et al, 2018;Martínez-Maestro et al, 2019). Additionally, Glu is also a major determinant for neuronal plasticity during periods of high neural activity as Glu influence the production of of brain-derived neurotrophic factor (BDNF) which regulates survival, differentiation and synaptogenesis in the CNS to change patterns of neuronal connectivity (Gonçalves-Ribeiro et al, 2019;Valtcheva and Venance, 2019).…”
Section: Possible Mechanisms Underly Metabolite Changesmentioning
confidence: 99%
“…The metabolic and neuronal processes are also tightly interlinked, with Glu existing in exchangeable pools. Increasing evidence demonstrates the close regulation between glucose consumption and glutamate-glutamine cycling (Sibson et al, 1998; Rothman et al, 2003), which leads to increasing Glu levels during the BOLD-activation period (Betina Ip et al, 2017; Vijayakumari et al, 2018; Martínez-Maestro et al, 2019; Ligneul et al, 2021). Additionally, Glu levels are also a major determinant for neuronal plasticity during periods of high neural activity (Gonçalves-Ribeiro et al, 2019; Valtcheva and Venance, 2019).…”
Section: Introductionmentioning
confidence: 99%